PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT DHARMA KRIDA SATRIA SPBU CILEDUG KARANG TENGAH KOTA TANGERANG - Nurholipah; Apriansyah, Muger (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the influence of work discipline and work motivation on employee performance at PT Dharma Krida Satria SPBU Ciledug, Karang Tengah, Tangerang City. The method used is quantitative descriptive. The sampling technique used saturated sampling, namely 50 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that work discipline has a significant effect on employee performance. By testing the hypothesis, t count > t table or (3.269 > 2.011). Work motivation has a significant effect on employee performance. By hypothesis testing, t count > t table (4,959 > 2,011). Work discipline and work motivation have a significant effect on employee performance with the regression equation Y = 13.276 + 0.208 X1 + 0.001 X2. The coefficient of determination value is 36.1%. Hypothesis testing obtained calculated F value > F table or (13,276 > 2,800).